Secondary oxalosis and sperm granuloma of the epididymis. Issue 5 (May 1994) - Coyne, J; al-Nakib, L; Goldsmith, D; O'Flynn, K
Abstract : A 30 year old man with a 20 year history of chronic renal failure who presented with a testicular lesion is described. The lesional pathology, secondary oxalosis, and associated sperm granuloma of the epididymis was clinically considered to be an intrascrotal tumour. The oxalate crystal deposition was present within the rete testis, the ductuli efferents, and the epididymis along with sperm granulomata. This seems to be a rare complication of secondary oxalosis associated with chronic renal failure and having both clinical and pathological implications.